Time And Dose- Dependent Effects Of Labisia Pumila On The Bone Strength Of Postmenopausal Osteoporosis Rat Model - Nadia Mohd Effendy; Shahrum Abdullah; Mohd Faridz Mod Yunoh; Ahmad Nazrun Shuid (BioMed Central, 2024)
Indexed by Scopus